How Does a Teacher's Multicultural Leadership Affect the Students' Moderation? A Study of Junior High School Students - Medianto Medianto; Taridi Taridi; Susanto Susanto; Dedi Kundana; Hendri Ardianto; Iin Avitasari; Widiyanto Widiyanto (International Journal of Science and Applied Science: Conference Series, 2024)
This study aimed to find the effect of multicultural leadership on religious moderation in student studies. The problems that occur are minority students feeling inferior, lack of awareness of the importance of respecting and accepting religious differences, lack of instillation of multicultural values and religious moderation, the presence of multi-ethnic students, the deepening of faith from students facilitated by the school, fair treatment of minority students. This study uses a quantitative approach, with the Random Sampling survey method, using a random system. A proportional allocation of 96 samples of 28 students was carried out to determine the sample size in each class. This study was conducted in a Private School with student respondents in the 2023/2024 academic year. The study showed a significant favorable influence between multicultural leadership and religious moderation with a t count of -17.559 and a significance value (p) of 0.001 <0.05. The simple regression analysis calculation results obtained the R Square value as 0.828. Multicultural leadership influences religious moderation by 82.8%, and other factors affect the remaining 17.2%.